ДЫХАТЕЛЬНАЯ ГИМНАСТИКА КАК ЭФФЕКТИВНОЕ СРЕДСТВО УКРЕПЛЕНИЯ ЗДОРОВЬЯ - Ешбаев, А.Ж.; Акимов, Н.Т. (SCIENCE and SOCIETY, 2018)
The acticle examines the value of respiratory gymnastics in physical education, improving human performance and strengthening of the body. The author of the article offers a set of breathing exercises, while,walking, running , cycling, playing, footboll.